Geografski informacijski sistemi - integrativna informacijska paradigma - Žalik, Borut (Geodetski vestnik, 2001)
The paper deals with geographic information systems (GIS) as an integrative paradigm of today's information society considered from three points of view: an integration of different data types, an accumulation of knowledge, and an integration of the users. different data types are characteristic for GIS, andeach of them has to be represented and considered in a specific way. Beacause more than 80% of today's data contain spatial component, the number of the users increases dramatically especially among non-traditional users of GIS. At the end, the importance of standardization in GIS as a base for globalization process and decisions is considered briefly.
Keywords: GIS; informacijski podatki; standardizacija